Peran Yayasan Anak Merdeka (Yama) dalam Meningkatkan Kesadaran Masyarakat pada Bidang Pendidikan - Nasution, Rahmad Rezeki (Program Pascasarjana IAIN Langsa, 2022)
Abstract. This study aims to describe the role of Anak Merdeka Foundation in increasing public awareness in the education sector in Tampur Paloh village, East Aceh. The method used in this research is qualitative research with a descriptive analysis approach and the type of research used in this research is phenomenology, then the data obtained from the informants were selected purposively, Among them are people who are directly involved in Anak Merdeka Foundation and the community of Tampur Paloh who became the object of research. Data collection is done by means of observation, interviews and documentation which researchers are directly involved in.The results of the study indicate that the role of the Anak Merdeka Foundation is: Helping the welfare of the community through education, the role of community assistance, organizes SMP and MA Merdeka as a means of learning for children in Tampur Paloh, facilitate alumni to study and invite the community to participate in school programs. Increased public awareness in the education sector can be seen from the large community participation in building schools, the community works together for schools, there is assistance from village funds for teachers, there is cooperation and mutual assistance between schools and the community and their efforts to save money to send their children to college.